Effect of graphene oxide on the mechanical and thermal properties of graphene oxide/hytrel nanocomposites. (January 2021) - Pandey, Neema; Tewari, Chetna; Dhali, Sunil; Bohra, Bhashkar S; Rana, Sravendra; Mehta, SPS; Singhal, Shailey; Chaurasia, Alok; Sahoo, Nanda Gopal
Polymer nanocomposites offer enhancement in thermomechanical and physicochemical properties of polymers with the presence of a little amount of nanostructured fillers such as carbon nanotubes, graphene, and layered silicates. A facile and rapid preparation of hytrel (HTL)-graphene oxide (GO) nanocomposites is done via a solution mixing method. The influence of GO content (0.1, 0.5, 1, 2, and 5 wt%) on mechanical and thermal properties of GO/HTL nanocomposites has been evaluated by using various techniques such as tensile testing, thermogravimetric analysis, differential scanning calorimetry, and dynamic mechanical analysis. The thermal stability and mechanical properties of GO/HTL nanocomposites were increased with increasing GO content. The composites have valuable improvement in tensile strength (139%) and storage modulus (72%) for HTL composite containing 5 wt% GO. The incorporation of GO into HTL polymer shows enhancement in thermal and mechanical properties due to the presence of strongest noncovalent interaction (π–π stacking) between the interface of nanocomposites. These enhanced physical properties of GO/HTL composites show its potential use in structural application.